2019
DOI: 10.1021/acsami.9b11536
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Titania Nanotube Surface Achieves UV-Triggered Charge Reversal and Enhances Cell Differentiation

Abstract: Stimuli-responsive biomaterials supply a promising solution to adapt to the complex physiological environment for different biomedical applications. In this study, a dynamic UV-triggered pH-responsive biosurface was constructed on titania nanotubes (TNTs) by loading photoacid generators, diphenyliodonium chloride, into the nanotubes, and grafting 2,3-dimethyl maleic anhydride (DMMA)-modified hyperbranched poly(L-lysine) (HBPLL) onto the surface. The local acidity was dramatically enhanced by UV irradiation for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…148,149 Some studies also explored the application of UV light as an in situ stimulus to improve the biological performance of titanium implants. Bai et al 104 reported an UV light-triggered dynamic titanium surface by loading photoacid generators (diphenyliodonium chloride, DPIC) in titania nanotubes (TNTs). Upon UV light irradiation for 30 seconds, enhanced local acidity by DPIC decomposed 2,3-dimethylmaleic anhydride (DMMA)-modified hyperbranched poly(L-lysine) (HBPLL), and consequently transformed surface chemistry from negatively charged caboxyl groups to positively charged amino groups.…”
Section: Photostimulation-responsive Strategiesmentioning
confidence: 99%
See 2 more Smart Citations
“…148,149 Some studies also explored the application of UV light as an in situ stimulus to improve the biological performance of titanium implants. Bai et al 104 reported an UV light-triggered dynamic titanium surface by loading photoacid generators (diphenyliodonium chloride, DPIC) in titania nanotubes (TNTs). Upon UV light irradiation for 30 seconds, enhanced local acidity by DPIC decomposed 2,3-dimethylmaleic anhydride (DMMA)-modified hyperbranched poly(L-lysine) (HBPLL), and consequently transformed surface chemistry from negatively charged caboxyl groups to positively charged amino groups.…”
Section: Photostimulation-responsive Strategiesmentioning
confidence: 99%
“…(1) Triggered antibacterial or anti-tumor drug release 25,97,98,[100][101][102][103][107][108][109][110][111][112][113] (1) Natural biomolecules (chitosan and silk fibroin) [97][98][99][100][101][102][103] (2) Conformation change of molecules (2) Surface potential changes promoting cell adhesion and osteogenesis [104][105][106] (2) Synthetic polymers (PMAA, DMMA and etc.) 25,104,105 (3) Cleavage of bonds/linkers (3) Inorganic molecules (MOFs, ZnO and etc.) [106][107][108] (4) pH-sensitive bonds/linkers 101,[108][109][110][111][112][113]…”
Section: Photostimulation-responsive Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Choosing proper aggregation state of nanoparticles and laser wavelength corresponding to the maximum absorption of NPs, one can locally cross-link the surface of films exposed to laser, Figure 2 (right). Even more drastic action of laser-nanoparticle interaction has been implemented in cell detachment [54], differentiation [55], and cell death induction [56]. However, this is not the only functionality of the nanoparticles in the coatings-they can be also used to control the masking for fabricating Janus particles.…”
Section: Passive and Active Activation Of Lbl Coatingsmentioning
confidence: 99%
“…Within aforementioned techniques, it is possible to produce thin polymeric membranes of large size and controllable fiber thickness, but although the fiber orientations can be adjusted, the tortuosity feature of the pores cannot be fully controlled. Electrochemical anodic oxidation is one of the cost- and time-efficient methods to fabricate highly orientated porous or/and nanotubular metal oxides such as titania, alumina, and zirconia surface arrays and membranes, even though it is not a lithographic fabrication technique. Due to their biocompatibility, photocatalytic activity, and antibacterial characteristic, anodic titanium dioxide (TiO 2 ) nanotubes (NTs) and their polymeric composites exhibit a reasonable potential in biological applications. …”
Section: Introductionmentioning
confidence: 99%